Impact of Fintech on Financial Performance of MSMES in Bali with Financial Literacy as Moderator - Ica Rika Candraningrat; Vera Intanie Dewi; Putu Ayu Kezia Dewi (Faculty of Economics and Business Udayana University, 2025)
This study examines the impact of fintech on the financial performance of micro, small, and medium enterprises(MSMEs) in Bali, with financial literacy as a moderating variable. A quantitative approach was employed,utilizing primary data collected through questionnaire distribution. The sampling method used was purposivesampling, with a total of 150 respondents. The findings indicate that fintech has a positive and significant effecton financial performance. Furthermore, financial literacy positively moderates this relationship, strengthening theimpact of fintech on financial performance. These results align with the Theory of Planned Behavior and theTheory of Financial Innovation. The higher the financial literacy of MSME owners, the more effectively theyutilize fintech to enhance financial performance.